The Conceptual and Hypothetical Model of Interactive Blended Problem Based Learning - Hansi Effendi; Yeka Hendriyani (Jurnal Pendidikan Indonesia, 2019)
This article discusses the results of research on the development of conceptual models and hypothetical models of Interactive Blended Problem Based Learning (IBPBL) in Programming Language subjects for Electrical Engineering students at Universitas Negeri Padang. This model is a blended learning model that combines face-to-face learning in class and Moodle-based online learning with problem-based learning syntax in the field of Electrical Engineering. The research was carried out in three stages: (1) literature review, (2) formulation of the conceptual model, and (3) formulation of the hypothetical model. The IBPBL conceptual models consist of: (1) philosophical components: pragmatism; (2) theoretical components: cognitivism, behaviorism, constructivism, and connectivism; (3) methodological components: problem-based learning; and (4) technical components: problem-solving, cooperation, critical thinking, innovative, creative and systematic. The hypothetical model is based on students' ability to solve problems critically, creatively, collaboratively, systematically by utilizing the various advantages possessed by face-to-face and online learning in Programming Language courses. Model validation is done using expert judgment. The expert assessment assessed the IBPBL model in three aspects, namely: (1) component sufficiency, (2) content, and (3) ease of implementation.